(untitled) (Journal of Engineering, 2025)
Seepage under earthen dams is considered a major factor in their stability. Statistics showed that 40% of dam failures are caused by foundation seepage. In this study, the finite element method was used to calculate the amount of seepage under (Haditha Dam, located on the Euphrates River. A simulation model was created for each decade, and the seepage amount was calculated for three decades. The results showed a match in the values and that the amount of seepage between the first and second decades increased by (0.000022 m3/s) or (7.62%). Seepage increased between the second and third decades by (0.000056 m3/s) or (17.89%). This increase is considered small for three decades and does not affect the dam’s stability. Therefore, with climate change and the decline in water supply sources, it is necessary to address this issue and find the best solution.